Anti-inflammatory activity of phenolic compounds from the whole plant of Scutellaria indica. Issue 5 (1st March 2015) - Cuong, To Dao; Hung, Tran Manh; Lee, Joo-Sang; Weon, Kwon-Yeon; Woo, Mi Hee; Min, Byung Sun
Graphical abstract